THE EFFECTS OF POLITICAL EVENTS AGAINST ABNORMAL RETURN AND TOTAL VOLUME SHARIA SHARES ACTIVITY THAT LISTED IN JAKARTA ISLAMIC INDEX (JII) - Rizka Zulfikar; Prihatini Ade Mayvita (University of Islam Malang, 2017)
This research is an event study that aims to discover whether there is any empirical evidence of the stock changed to one of the political events in Indonesia. This research used a political event namely Jakarta Governor Election 2017 Round II, by using indicator value of abnormal return and Trading Volume Activity Sharia stocks in Jakarta Islamic Index Stock Market. This event political event was held on April 19, 2017. Population and sample in this research are 30 sharia stocks in JII. The data used in this research are secondary data consists of consists of daily stock prices, daily share trading volume, and daily stock prices index during the five days before, one day at the time of, and five days after the event. Statistical tool used to test the hypothesis is t test and Wilcoxon Signed Rank Test. T test calculation results indicate that there are significant positive value of abnormal return at a few days around the event date, which means the market responds to this event as a good news. While the results of Wilcoxon Signed Rank Test prove that there are significant differences between the average abnormal return in the period before the time the event and in the period after the time event, but not significant in the period before- after the event. The results of Wilcoxon Signed Rank Test also shows that there are significant differences between the average trading volume activity in the period at the time of-after the event, but not significant in the period before-at the time event and before-after the event.